PENGARUH FASILITAS DAN PELAYANAN KARYAWAN TERHADAP KEPUASAN PENGUNJUNG PADA TAMAN WISATA QWEEN - Al Hidayat, Rahmat; Eka Putra, M. Bima; Cahya Pradipta, Ryan (STIA Bengkulu, 2024)
The purpose of this research is to determine the effect of facilities on visitor satisfaction (at Qween tourist park, Betungan Village, Bengkulu City), to determine the effect of employee service on visitor satisfaction (at Qween tourist park, Betungan Village, Bengkulu City), to determine the effect of facilities and employee service on visitor satisfaction (at the Qween tourist park, Betungan Village, Bengkulu City), to determine the magnitude of the influence of employee facilities and services on visitor satisfaction (the Qween tourist park, Betungan Village, Bengkulu City). Sampling in this study used the accidental sampling technique, which is a technique for determining samples based on chance, that is, anyone who happens to meet the researcher can be used as a sample. Data collection methods include observation, documentation, literature and questionnaires. Data analysis techniques using classical assumption tests, multiple linear regression tests and hypotheses. The research results showed that facilities significantly influence visitor satisfaction at the Qween tourist park, Betungan Village, Bengkulu City. This is shown by the significance value of 0.000 < 0.05. Employee service significantly influences visitor satisfaction at the Qween tourist park, Betungan Village, Bengkulu City. This is shown by the significance value of 0.000 < 0.05. Employee facilities and services explain changes in the consumer satisfaction variable by 76.2%, while the remaining 23.8% is explained by other factors outside the model.